2011
DOI: 10.1093/ecam/nen075
|View full text |Cite
|
Sign up to set email alerts
|

The Knowledge, Attitudes and Usage of Complementary and Alternative Medicine of Medical Students

Abstract: The increasing use of CAM by patients has led to an increase in teaching about CAM in medical school in the US. In preparation for initiation of a new curriculum in Integrative Medicine at the David Geffen School of Medicine at UCLA a cross sectional survey was used to assess medical students': (i) familiarity, (ii) opinions, (iii) personal use and (iv) willingness to recommend specific CAM modalities, using a five point Likert scale of an established measure. A total of 263 first, second and third year medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 36 publications
(24 reference statements)
4
35
0
6
Order By: Relevance
“…In fact, some universities have incorporated CAM training into their medical curricula. [6][7][8] However, this is not widespread in other countries although in recent years, it has been reported that medical students across the globe, including the United Kingdom, Singapore, and Germany, have an interest in increasing their knowledge of CAM in addition to conventional medicine.…”
Section: Cam Studies In Medical Studentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, some universities have incorporated CAM training into their medical curricula. [6][7][8] However, this is not widespread in other countries although in recent years, it has been reported that medical students across the globe, including the United Kingdom, Singapore, and Germany, have an interest in increasing their knowledge of CAM in addition to conventional medicine.…”
Section: Cam Studies In Medical Studentsmentioning
confidence: 99%
“…6,9,10,12 The first part of the survey instrument incorporated a question on the religion of the participants. Survey data were merged with existing student profile data to provide a demographic profile including gender, course and year of medical school, age, and nationality.…”
Section: Questionnairementioning
confidence: 99%
“…Esta proporção, maior que a de oito dos estudos analisados 9,11,[13][14][15][16][17][18] , pode indicar interesse dos sujeitos de pesquisa com relação a este tema, visto que a participação no estudo foi voluntária.…”
Section: Discussionunclassified
“…Estes dados vão contra o esperado de acordo com a revisão da literatura, que demonstrou declínio das atitudes favoráveis ao longo do curso de Medicina 11,15,21,25 . Este fato tem sido explicado pela tendência dos estudantes dos estágios iniciais a exibir maior idealismo 21 , que seria perdido devido à exposição deles às atitudes negativas com relação às terapias complementares durante o treinamento clínico 12 .…”
Section: Discussionunclassified
“…The study has shown that students at different level have different level of knowledge (Table 3). There is a need for integrative curriculum [16,17]. Both lectures and direct shadowing appear to be the favorable methods for students.…”
Section: Discussionmentioning
confidence: 99%